PENGARUH KOMPENSASI, MOTIVASI KERJA, DAN LINKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi pada PT. Kereta Api Indonesia Di Surakarta Cabang Solo Balapan). - Galuh Mujaro Faitul; Kusdiyanto Kusdiyanto (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2023)
The purpose of this study is to examine the impact of compensation, motivation, and working conditions on the employment of PT Kereta Api Indonesia employees in Surakarta's Solo Balapan district. This survey's methodology is quantitative, with a sample size of 37 respondents. Data collection methods using slow, steady pengisian angkets. The analysis was conducted using the SmartPLS 3.0 application, and the results showed that the variable compensation did not significantly and positively affect the karyawan's work. Variable work motivation has a positive and significant impact on an employee's career path. Positive and significant change in the working environment has an impact on the employee's job performance.